Modulatory Effect of Intermittent Fasting on Adipose Tissue Inflammation: Amelioration of Cardiovascular Dysfunction in Early Metabolic Impairment - Dwaib, Haneen S.; AlZaim, Ibrahim; Eid, Ali H.; Obeid, Omar; El-Yazbi, Ahmed F. (Frontiers in Pharmacology, 2021)
Cardiometabolic syndrome (CMS) is a cluster of maladaptive cardiovascular, renal, thrombotic, inflammatory, and metabolic disorders. It confers high risk of cardiovascular mortality and morbidity. CMS is triggered by major shifts in lifestyle and dietary habits with increased consumption of refined, calorie-dense diets. Evidence indicates that diet-induced CMS is linked to Adipose tissue (AT) inflammation. This led to the proposal that adipose inflammation may be involved in metabolic derangements, such as insulin resistance and poor glycemic control, as well as the contribution to the inflammatory process predisposing patients to increased cardiovascular risk. Therefore, in the absence of direct pharmacological interventions for the subclinical phase of CMS, time restricted feeding regimens were anticipated to alleviate early metabolic damage and subsequent comorbidities. These regimens, referred to as intermittent fasting (IF), showed a strong positive impact on the metabolic state of obese and non-obese human subjects and animal models, positive AT remodeling in face of overnutrition and high fat diet (HFD) consumption, and improved CV outcomes. Here, we summarize the available evidence on the role of adipose inflammation in triggering cardiovascular impairment in the context of diet induced CMS with an emphasis on the involvement of perivascular adipose tissue. As well, we highlight the possible molecular pathways linking intermittent fasting to the ameliorative effect on adipose inflammation and cardiovascular dysfunction under such circumstances. We highlight a number of targets, whose function changes in perivascular adipose tissue inflammation and could be modified by intermittent fasting acting as a novel approach to ameliorate the inflammatory status.